5G Technology: A New Step to IoT Platform - S.I. Yusifov; N.A. Ragimova; V.H. Abdullayev; Z.B. Imanova (Yayasan Ahmar Cendekia Indonesia, 2020)
The article is dedicated to the study of 5G technology, the name of which we have heard a lot recently. This technology is one of the most talked about technologies of recent times. 5G has entered our lives as the latest and fastest version of mobile networks. Here's a look at how 5G technology came into our lives, how it has captured the attention of users, and finally, what they think about the technology. In addition, what areas are affected by this technology, in particular, its impact on the IoT field has been studied and key theoretical information has been provided.